Poverty and exclusion in a global world - Bhalla A S; Lapeyre Frederic (Hampshire Palgrave, 2004)
This volume looks at the three dimensions of social exclusion: economic, social and political. Exclusion is analyzed as a new approach to such issues as the 'new' poverty, precariousness, long-term unemployment, social polarization and lack of citizenshi
Keywords: People with social disabilities; Poverty; Social isolation; Social marginality